Cooperation and conflict GDR theatre censorship, 1961-1989 - Bradley, Laura J. R. (Oxford : Oxford University Press, 2010)
This study explores how theatre was censored in the GDR from 1961 to 1989. By examining a range of case studies, from banned stagings to those that met with official approval, it reveals the shifting patterns of cooperation and conflict that shaped the space for theatrical experimentation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Theater -- Censorship -- Germany (East); Theater and state -- Germany (East); Theater -- Germany (East)